2011
DOI: 10.2337/dc10-2197
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Endotoxin Activity in Human Serum Is Associated With Dyslipidemia, Insulin Resistance, Obesity, and Chronic Inflammation

Abstract: OBJECTIVETo investigate whether bacterial lipopolysaccharide (LPS) activity in human serum is associated with the components of the metabolic syndrome (MetS) in type 1 diabetic patients with various degrees of kidney disease and patients with IgA glomerulonephritis (IgAGN).RESEARCH DESIGN AND METHODSSerum LPS activity was determined with the Limulus Amoebocyte Lysate chromogenic end point assay in type 1 diabetic patients with a normal albumin excretion rate (n = 587), microalbuminuria (n = 144), macroalbuminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
229
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(255 citation statements)
references
References 26 publications
14
229
0
7
Order By: Relevance
“…Similar results were found when the gut microbiome of human twins discordant for obesity was transferred to germ-free mice [34]. Furthermore, studies in mice and in humans have shown that gut bacteria may contribute to other components of the metabolic syndrome, such as insulin resistance and type 2 DM through elevated levels of LPS [5,6], leading to an inflammatory state in the host [7,31,35].…”
Section: Discussionsupporting
confidence: 68%
“…Similar results were found when the gut microbiome of human twins discordant for obesity was transferred to germ-free mice [34]. Furthermore, studies in mice and in humans have shown that gut bacteria may contribute to other components of the metabolic syndrome, such as insulin resistance and type 2 DM through elevated levels of LPS [5,6], leading to an inflammatory state in the host [7,31,35].…”
Section: Discussionsupporting
confidence: 68%
“…11 Those increased endotoxin levels may further trigger inflammatory reactions and/or immune dysfunction. 12 This is also underlined by impaired cell-mediated immune responses in vivo and in vitro and a reduced intracellular killing by neutrophils. 13 Weight loss is the most effective therapy of obesity, which also influences gut microbiota composition 14 and improves monocyte function.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, clinical studies have shown that circulating LPS is increased in patients with obesity (21,33), and animal studies have shown that TLR4 deficiency in mice protects against the development of insulin resistance (41). Taking these clinical and animal findings together, it is indicated that TLR4 signaling triggered by low concentrations of LPS may contribute to the inflammatory state that is essential for developing insulin resistance (50).…”
mentioning
confidence: 99%